Psychological and ethical ideas : what early Greeks say - Sullivan, Shirley Darcus, 1945- (Mnemosyne, Supplements, 1995)
Psychological and Ethical Ideas studies what Greek poets and philosophers of the Archaic Age of Greece say about certain psychological and ethical ideas. These ideas include "psychological activity", "soul", "excellence", and "justice". These ideas were chosen to show how early Greek individuals think, act, and relate to other people and to their universe. The book first discusses the nature of the literature of the Archaic Age. It then treats in detail what early Greeks say about the four ideas, presenting numerous quotations (all in translation). The book concludes with an overview of the ideas discussed. The book introduces the reader to important ideas of the Archaic Age, showing what both poets and philosophers thought. These ideas are central to this period and were to have an important role in the literature and philosophy of later Greek authors, especially in the drama of the fifth century and the philosophy of the fourth century.